The Effect of Delayed Cord Clamping (DCC) on Haemoglobin Levels and Oxygen Saturation Levels in Newborns - Ilmiyani, Siti Naili; Yanti, Eka Mustika; Siswari, Baiq Disnalia (Babali Nursing Research, 2023)
Background: The case of iron deficiency anaemia in infants is a serious health problem because it interferes with mental and cognitive development. DCC prolongs blood flow from the placenta to the baby through the umbilical cord, increases blood volume, and optimizes oxygen transfusion which might prevent anemia and promote effective self-breathing. Objective: To determine the effect of DCC on Haemoglobin Levels and Oxygen Saturation Levels in Newborns. Method: Experimental research with Post-test Only Control Group design. The total Sampling method was used on 30 newborns as the samples, with 15 intervention groups and 15 control groups. Data collection used the Delayed Cord Clamping procedure, observation sheets, Easy Touch GCHb tool, and Baby SpO2. An Independent T-test was used to process the data. Results: Based on the experiment on 30 infants, it found that the average hemoglobin level of new-borns with the Delayed Cord Clamping treatment was 22.07 gr/dL higher than the hemoglobin level of new-borns without the Delayed Cord Clamping treatment of 17.79 gr/dL. In addition, the average oxygen saturation level of newborns with the Delayed Cord Clamping treatment was 87.4% more than that of newborns without the Delayed Cord Clamping treatment of 77.4%. Conclusion: DCC affects Haemoglobin Levels and Oxygen Saturation Levels in Newborns in the Work Area of the Aikmel Regional Health Centre. There is a need to increase information about the benefits of DCC among health workers.